2018
DOI: 10.1109/tcomm.2018.2851593
|View full text |Cite
|
Sign up to set email alerts
|

Cache-Enabled HetNets With Millimeter Wave Small Cells

Abstract: In this paper, we consider a novel cache-enabled heterogeneous network (HetNet), where macro base stations (BSs) with traditional sub-6 GHz are overlaid by dense millimeter wave (mmWave) pico BSs. These two-tier BSs, which are modeled as two independent homogeneous Poisson Point Processes, cache multimedia contents following the popularity rank. High-capacity backhauls are utilized between macro BSs and the core server. In contrast to the simplified flat-top antenna pattern analyzed in previous articles, we em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Proof: As NLOS interferences are ignored, ρ N (v) should be removed from Lemma 4. Moreover, when α L = 2, ρ L (v) can be simplified by using the similar method as discussed in the Appendix A of [49]. Lastly, utilizing the similar proof method as Lemma 4, the simpler equation than (22) can be expressed in (26).…”
Section: ) Laplace Transform Of Interferencesmentioning
confidence: 99%
“…Proof: As NLOS interferences are ignored, ρ N (v) should be removed from Lemma 4. Moreover, when α L = 2, ρ L (v) can be simplified by using the similar method as discussed in the Appendix A of [49]. Lastly, utilizing the similar proof method as Lemma 4, the simpler equation than (22) can be expressed in (26).…”
Section: ) Laplace Transform Of Interferencesmentioning
confidence: 99%
“…Furthermore, machine learning approaches were introduced in [16] to configure beamforming patterns. Note that the average performance of networks is an important metric for designing new protocols [18]. Although the mentioned results based on measurements or simulations are inspiring, it is not efficient to evaluate the average performance of mmWave V2X networks via the same methods.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…For traditional mmWave networks and vehicular communications, stochastic geometry has already been widely utilized [18,[20][21][22][23][24][25][26][27]. The authors in [20] modeled line-of-sight (LOS) and non-LOS (NLOS) base stations (BSs) as two independent thinning Poisson point processes (PPPs) to evaluate the coverage and rate performance of cellular networks.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…Under this condition, the signal-to-interferenceplus-noise (SINR) coverage probability with decoupled cell association strategy was studied in [14], and it is observed that extremely high small cell association weight is desirable for mmWave SCells. The authors in [15] analyzed the the performance of catch-enable hybrid heterogeneous networks under the similar deployment settings, where the cached multimedia contents following the popularity rank, and it is shown that the integrated Sub-6GHz and mmWave HetNet is interference-limited and outperforms the traditional HetNet. The hybrid cellular network with ultra high frequency and mmWave BSs were investigated in [16] by using experimental data in a university campus.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, the existing works that considering integrated Sub-6GHz BSs and mmWave BSs usually model each tier of BSs as a PPP [14], [15], while the studies that consider spatial coupling between BSs and UEs in heterogeneous networks assume the operations on the same frequency band [22]- [24]. Different from previous works, we take both different frequency bands and aforementioned coupling in traffic hotspots into consideration.…”
Section: Introductionmentioning
confidence: 99%